Effects of VAK Learning Style Preferences on Senior School Students’ Performance in Chemistry in Ilorin, Nigeria - SALIHU, Hauwa Ajibola; AMEEN, Khadijat Saka (Ilorin Journal of Education, 2025)
The study determined the effects of VAK learning style preferences on senior school students’ performance in isomerism. The study employed a quasi-experimental, non-randomized, non-equivalent pretest-posttest control group design. Two senior schools were purposively selected from Ilorin South Local Government Area, Kwara State, Nigeria. 111 participants were drafted into the visual, auditory and kinesthetic (VAK) classrooms and 86 participants into the control classroom with a Preferred VAK Chemistry Classroom Checklist (PVC3). Data was collected with the Isomerism Assessment Test for pretest and was reshuffled for the posttest. Additional data was collected using the Perception of Learners on VAK Classrooms Questionnaire (PLVCQ). Reliability indices of 0.77 and 0.79 were obtained for the IAT and PLVCQ, respectively, using Many-Facet Rasch Measurement (MFRM) and Cronbach’s Alpha. Research questions were answered using percentage, mean and standard deviation, while hypotheses were tested using ANCOVA at 0.05 significant level. Findings revealed that there was no significant difference in performance among the three VAK classrooms but a significant comparative effectiveness in performance of learners in all the VAK classrooms against the control group. In addition, all the learners perceived the learning intervention to be relevant to their study. The study concluded that VAK learning styles are effective for learning isomerism. The study, therefore, recommended that learners should be encouraged to choose and use their preferred learning style to study, in pursuit of a better academic performance.